The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.2463/mrms.mp.2017-0001
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Contrast Enhancement of the Perivascular Space in the Basal Ganglia and Endolymphatic Volume Ratio

Abstract: Purpose:We routinely obtain the endolymphatic hydrops (EH) image using heavily T2-weighted three dimensional-fluid attenuated inversion recovery (hT2w-3D-FLAIR) imaging at 4 hours after intravenous administration of a single-dose of gadolinium-based contrast media (IV-SD-GBCM). While repeating the examination, we speculated that the contrast enhancement of the perivascular space (PVS) in the basal ganglia might be related to the degree of EH. Therefore, the purpose of this study was to investigate the relation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 21 publications
0
13
1
Order By: Relevance
“…Intravenously administered GBCAs are reported to leak into the CSF even in healthy subjects ( 33 ). At approximately 4 hours after intravenous injection of gadolinium, transfer of gadolinium into the CSF and Virchow-Robin space at the base of the brain can be observed on heavily T2-weighted fluid-attenuated inversion recovery images ( 34 35 36 37 38 ). It is also interesting that intravenously administered GBCAs show leakage from the cortical veins with delayed imaging after injection, with the leakiness of the cortical veins significantly correlated with age ( 39 ).…”
Section: Imaging Evaluation Of the Glymphatic System/neurofluid Dynammentioning
confidence: 99%
“…Intravenously administered GBCAs are reported to leak into the CSF even in healthy subjects ( 33 ). At approximately 4 hours after intravenous injection of gadolinium, transfer of gadolinium into the CSF and Virchow-Robin space at the base of the brain can be observed on heavily T2-weighted fluid-attenuated inversion recovery images ( 34 35 36 37 38 ). It is also interesting that intravenously administered GBCAs show leakage from the cortical veins with delayed imaging after injection, with the leakiness of the cortical veins significantly correlated with age ( 39 ).…”
Section: Imaging Evaluation Of the Glymphatic System/neurofluid Dynammentioning
confidence: 99%
“…Various studies have shown that GBCAs distribute in various fluid spaces such as the CSF, the perilymph of the inner ear, the perivascular spaces of the basal ganglia, the meningeal lymphatics and the brain parenchyma after IV administration. [1][2][3][4][5]9,[14][15][16][17][18][19][20] The pattern for the intracranial distribution of intravenously administered GBCA might be associated with aging, blood-brain barrier (BBB) integrity, function of glymphatic system, and renal function. 2,3,21,22 The glymphatic system is the waste clearance system of the brain and has attracted much attention from a wide range of investigators.…”
Section: Introductionmentioning
confidence: 99%
“…Contrast enhancement on the delayed hT 2 -FL images has been reported in the PVSs of the BG. 10 , 24 However, a lack of enhancement of the extremely large PVS in the BG using the same technique has also been reported. 28 Scan timing after IV-SD-GBCA might be a future topic of research for the visualization of enhancement in the various PVSs.…”
Section: Discussionmentioning
confidence: 99%
“… 21 , 22 The glymphatic system is speculated as a route for gadolinium penetration into the brain. 10 , 23 , 24 Therefore, a better understanding of the function of PVSs is quite important, not only for general neuroscience research, but also to address specifically the issue of gadolinium deposition in the brain. There are multiple reports regarding differences between the PVS BG and the PVS WM .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation